Sustainability of centralized contract farming among tobacco smallholder farmers in Makoni North District, Zimbabwe - Bernard Chazovachii (Cogent Social Sciences, 2021)
The study explores centralized contract farming sustainability among tobacco smallholder farmers in Zimbabwe. Despite studies on centralized contract farming to date, little has been theorized with regard to its sustainability. Using mixed-method research, questionnaires, key informant interviews, document review and focus group discussions were employed in gathering data from farmers, Extension Officers and field officers of the contracting firms. Using Pearson Correlation Coefficient and thematic analysis findings revealed that centralized contract tobacco farming is unsustainable. Institutional contract arrangements are manipulative and are unwelcome to farmers. Economically, contracting firms find it viable as they obtain more profit at the expense of smallholder farmers. Although farmers are assured of inputs, extension service and market for the product, the contract terms are characterized by transaction cost, uncertainty and information asymmetry. Moreso, although financial and physical assets ownership have been increased, human, natural and social capital are a challenge. Shocks, stresses and seasonality still characterize the vulnerability context of the farmers as society has been exposed to women and child abuses, food insecurity, and social decay. The study therefore recommends an increased participatory action and learning in crafting and implementing contract terms by farmers, state and non-state actors for sustainability to be realized.